The Use of Game Theory in Regional Economics: a quantitative retrospective - Sandra Silva; Isabel Mota; Filipe Grilo (European Regional Science Association (ERSA), 2011)
The construction of formal models that deal with space observed a huge increase since the late 1980s. As Fujita et al. (1999) stress, the field of regional economics experienced a revival with the emergence of new analytical tools such as the diffusion of imperfect competition models, networks and mathematical programming. One of the most powerful tools within social science in general and economics in particular is game theory. This methodology allows for the formal analysis of the interactions among economic agents and, therefore, it is particularly useful for the study of economic decisions regarding spatial issues such as the location choices of firms and households; infrastructures, transports and communications; regional and urban policy; innovation and regional development; and regional labour markets. For this reason, a concrete, quantitative systematization of the use of this tool on regional economics research seems to be a relevant topic in the agenda concerned with progress in regional science. In this paper we study research in regional economics and provide a quantitative retrospective of the use of game theory in this field. Our main goal is twofold. First, we intend to categorize the contributions in the use of this analytical tool - by main research subjects, by authors' affiliations, by journal, etc. - using a bibliometric approach. Second, by analysing co-authoring and using Social Network Analysis, we want to test the existence of structures upon which distinct co-authorship emerges. In broader terms, the results of this research will provide a framework for analyzing the potential use of game theory in regional economics, suggesting new future research directions.
Keywords: 330